T11TS immunotherapy repairs PI3K‐AKT signaling in T‐cells: Clues toward enhanced T‐cell survival in rat glioma model. Issue 2 (11th July 2017) - Chaudhuri, Suhnrita; Singh, Manoj K.; Bhattacharya, Debanjan; Datta, Ankur; Hazra, Iman; Mondal, Somnath; Faruk Sk Md, Omar; Ronsard, Larance; Ghosh, Tushar K.; Chaudhuri, Swapna
Abstract : Malignant glioma is the most fatal of astrocytic lineage tumors despite therapeutic advances. Onset and progression of gliomas is accompanied by severe debilitation of T‐cell defense and T‐cell survival. One of the chief contributors to T‐cell survival downstream of activation is the PI3K‐AKT pathway. Our prior studies showed that the novel immunotherapeutic molecule T11‐target structure (T11TS) blocks T‐cell apoptosis in glioma. We also showed activation of immunological synapse components and calcineurin‐NFAT pathway following T11TS immunotherapy of glioma‐bearing rats. This lead to investigations whether such T‐cell activation upon T11TS therapy translates into activation of downstream PI3K/AKT signals which may be related to observed blockade of T‐cell apoptosis. For the purpose, we assessed by flowcytometry and immunoblotting, expressions of PI3K, PDK1, AKT, p‐AKT, and PTEN in splenic T‐cells of normal, experimentally‐induced glioma‐bearing rats and glioma‐bearing rats receiving first, second and third doses of T11TS. We also determined comparative nuclear translocation of NF‐κB across groups. We found significant increases in T‐cell expressions of PDK1, PI3K, and p‐AKT in T11TS‐treated animal groups compared to sharp downregulations in glioma. AKT levels remained unchanged across groups. PTEN levels declined sharply after T11TS immunotherapy. T11TS also caused enhanced NF‐κB translocation to the T‐cell nucleus compared to glioma group. Results showed heightened activation of the PI3K‐AKT pathway in glioma‐bearing rats following T11TS immunotherapy. These results illustrate the novel role of T11TS immunotherapy in ameliorating the PI3K pathway in T‐cells in glioma‐bearing animals to enhance T‐cell survival, according greater defense against glioma. The study thus has far‐reaching clinical outcomes. Abstract : In glioma‐bearing rats, T11TS switches on TCR/CD28 signals in T‐cells to activate receptor tyrosine kinase (RTK) signals. This gives rise to activation of PI3K and PDK1, inhibition of PTEN and consequent phosphorylation and activation of AKT. AKT activation causes nuclear translocation of NF‐κB, which affects transcription of key genes associated with T cell survival.